Optimizing energy harvesting from waste motor oil through steam reforming: A path to efficient combustion and emissions reduction - Bambang Pujiarto; Nofa Ardana; An’nisa Solihah; Muhammad Latifur Rochman; Ahmad Tresno Adi; Budi Waluyo (Universitas Muhammadiyah Magelang, 2023)
Waste Motor Oil (WMO) is a hazardous waste material with the potential to contaminate water, soil, and the atmosphere. The management and engineering of WMO have become imperative in modern society for both resource utilization and environmental protection. Maximizing the energy content of WMO poses a significant challenge for researchers, to solve environmentally friendly solutions. Direct combustion of WMO often results in incomplete combustion and elevated CO emissions. Therefore, this research aims to optimize the harnessing of WMO's energy potential through a furnace equipped with steam injection. The steam is generated by utilizing the heat energy produced during the WMO heating process. Our study demonstrates that steam injection in the WMO furnace is an effective method for maximizing energy content while simultaneously reducing CO emissions.